Methyl Donors Inhibit Panc-1 Cell Proliferation by Decreasing NFkB and Erk Signaling Levels and Raising E-Cadherin Expression - Eva Kiss; Gertrud Forika; Istvan Takacs; Tibor Krenacs; Zsuzsanna Nemeth (Current Practice in Medical Science Vol. 8, 2022)
We hypothesized that dietary methyl-donors may improve the physiology of cancer patients including those with pancreatic cancer, and could be used for intervention therapy. In this study, methyl-donor treatment (L-methionine, choline chloride, folic acid and vitamin B12) of an aggressive pancreatic adenocarcinoma cell line (Panc-1) resulted in significantly increased p21WAF1/Cip1 cyclin dependent kinase inhibitor levels along with the apoptotic SubG1 fractions and at the same time, phospho-Erk1/2 levels and the proliferation rate were significantly reduced. An aggressive cancer with a high risk of metastasizing like pancreatic cancer, diet is one of the lifestyle-related variables in its genesis. Methyl-donors are dietary micronutrients that support key metabolic pathways and operate as bioactive food components by supplying methyl groups as cofactors and substrates. Imbalanced nutritional status of methyl-donors has recently been linked to pathological conditions. Though methyl donor treatments also increased the pro-apoptotic protein Bak, Puma and Caspase-9, failed to elevate cleaved Caspase-3 levels. In addition, the treatment significantly reduced the production of the pro-inflammatory cytokine IL-17a and the transcription factor NFkB. SDF-1a and VEGF levels were found to be significantly lower after methyl-donor treatmtnts, which may signify a decreased risk of metastatic spread. E-cadherin expression increased after the methyl-donor therapy, as was predicted, and was inversely related to these alterations. It is concluded that methyl-donors may have the potential to reduce aggressive and proliferative phenotype of Panc-1 cells. This suggests a promising role of dietary methyl-donors for complementing relevant cancer therapies even in treatment resistant pancreatic adenocarcinomas.